Hydrothermal post-treatment of digestate to maximize the methane yield from the anaerobic digestion of microalgae. (January 2018) - Nuchdang, S.; Frigon, J.-C.; Roy, C.; Pilon, G.; Phalakornkule, C.; Guiot, S.R.
Graphical abstract: Highlights: Anaerobic digestibility of raw microalgae is limited. Digestate was treated by wet oxidation (WetOx) and hydrothermal carbonization (HTC). Both WetOx and HTC resulted in a substantial solids solubilization. Biomethane potential of the hydrothermally treated digestate increased up to 3 times. Digestate post-treatment may improve the anaerobic digester overall CH4 yield by 40%. Abstract: As an alternative to applying the hydrothermal treatment to the raw algal feedstock before the anaerobic digestion (i.e. pre-treatment), one considered a post-treatment scenario where anaerobic digestion is directly used as the primary treatment while the hydrothermal treatment is thereafter applied to the digestate. Hydrothermal treatments such as wet oxidation (WetOx) and hydrothermal carbonization (HTC) were compared at a temperature of 200 °C, for initial pressure of 0.1 and 0.82 MPa, and no holding time after the process had reached the temperature setpoint. Both WetOx and HTC resulted in a substantial solids conversion (47–62% with HTC, 64–83% with WetOx, both at 0.82 MPa) into soluble products, while some total chemical oxygen demand–based carbon loss from the solid-liquid phases was observed (20–39%). This generated high soluble products concentrations (from 6.2 to 10.9 g soluble chemical oxygen demand/L). Biomethane potential tests showed that these hydrothermal treatments allowed for a 4-fold improvement of the digestate anaerobic biodegradability. The hydrothermal treatments increased the methane yield to about 200 LSTP CH4 /kg volatile solids, when related to the untreated digestate, compared to 66 LSTP CH4 /kg volatile solids, without treatment.